PRESENT AND FUTURE: INDIVIDUALS AND HOUSEHOLDS IN A SOUTHERN ITALIAN CITY - Sacco, Giuseppina; Sacco, Pietro (European Scientific Journal, ESJ, 2015)
The link between social and demographic phenomena concerning a population of a given territory is the representative essence of every social organism. Effectively, it is not difficult to understand why in complex societies like ours we need to get as much information as possible, which has become essential in order to make the decisions that will influence future choices. The aim of this survey is to carry out population projections of the city of Bari, by sex and age, in order to know the future demographic scenarios of Bari population and the household ones resulting from them. Concerning this, two possible scenarios will be shown. The first one by hypothesizing constant mortality and fecundity with migrations equal to zero. Obviously that means straining the reality, but it is really useful in order to evaluate the future evolution of the population due to the action of the sole natural components. The second one, by hypothesizing constant migrations throughout the observation period, has an effective role when we analyze the effects of migratory drift on the evolution dynamics of the population analysed in this survey.